Consortium for e-Resources in Agriculture - Visakhi, P. (DESIDOC Journal of Library & Information Technology, 2010)
Consortium for e-Resources in Agriculture is a e-Consortium of Agricultural Libraries under the Indian Council of Agricultural Research for National Agricultural Research System libraries. The National Agricultural Research System of India comprises Indian Council of Agricultural Research and Central/State Agricultural Universities under Department of Agricultural Research and Education, Ministry of Agriculture, Govt of India. The paper discusses the background, main features, and advantages of the consortium for e-resources in Agriculture. http://dx.doi.org/10.14429/djlit.29.266